DEVELOPMENT OF ARTISTIC AND CREATIVE SKILLS IN PRIMARY SCHOOL CHILDREN USING WATERCOLOR PAINTING (American Journal of Technology and Applied Sciences, 2025)
This article examines the development of artistic and creative skills in primary school children through watercolor painting. It analyzes the specific perceptions of color, form, and space in children of this age group, revealing the pedagogical potential of watercolor as an expressive and accessible artistic medium. Particular attention is paid to methodological approaches to developing creative thinking and aesthetic perception.